Analisis Evapotranspirasi Metode Penman Modifikasi Dan Thornthwaite Terhadap Pemodelan Debit Fj. Mock: Analysis Of Evapotranspiration Using Modified Penman And Thornthwaite Methods On Fj. Mock's Run-Off Modelling - Baskoro, Ari Yudha; Suripin, Suripin; Suprapto, Suprapto (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Evapotranspiration is a key parameter used in run-off modelling. The Bulango Ulu Dam, located near the equator where sunlight is at its peak throughout the year, makes evapotranspiration a crucial factor in analysing water availability. This research aims to analyse the performance of two evapotranspiration calculation methods on the accuracy of run-off modelling to the Bulango Ulu dam. The study employs the modified Penman and Thornthwaite evapotranspiration methods as input to Mock's model. The Analysis indicates that the Mock-Penman method outperforms the Mock-Thornthwaite method, with statistical parameter results of MAE 0.963, NSE 0.891, R 0.949 and Kr 1.3%, Therefore, it concludes that the run-off modelling aligns with the observed flow value